The Students' Perspective of Quizizz As English Language Assessment Media - Harisha, Nurul; Oktaviana , Fadilla (English Education, Linguistics, and Literature Journal, 2024)
Quizizz is an educational game application that has gained popularity as a learning tool in recent years. The aim of this study is to find out students' perspectives on using Quizizz as an English language assessment media. Subjects in this study were two 6th grade elementary school students with the initials FA and MA. This research approach used descriptive Qualitative Research with observation and interviews. This study found that students had positives perspective towards Quizizz as English language assessment. Next, found out that students enjoyed using Quizizz, finding it fun and interesting. They also felt that Quizizz made it easier for them to take tests and increased their interest in learning English. The study also found that Quizizz helped to increase students' knowledge of English. The study concludes that Quizizz is an effective and enjoyable platform for language assessment, providing an engaging and interactive learning experience.